Anatomical and ultrasound‐based injections for sunken upper eyelid correction. (21st June 2019) - Tansatit, Tanvaa; Phumyoo, Thirawass; Jitaree, Benrita; Sahraoui, Yasmina M. E.; Lee, Joo Heon
Abstract: Background: A needle or a cannula can be safely used during filler injection procedures to correct a sunken upper eyelid. To date, there are no precise injection points recommended that are based on an anatomical study. Objective: This study systematically investigated the vascular pattern and depth of forehead arteries at the periorbital area of upper eyelid. Methods: Twenty cadavers were dissected in this study. Additional data were obtained from 30 healthy volunteers using Doppler ultrasound imaging with high‐frequency probe. Results: The ophthalmic artery divided into two opposite primary branches: the superior and inferior orbitoglabellar arteries running along the orbital rim. After the supratrochlear artery arose from the superior orbitoglabellar artery at the medial eyebrow, the supraorbital artery either divided from this artery near the supraorbital foramen or emerged as an individual artery from the supraorbital notch. The inferior orbitoglabellar artery gave off the radix artery superior to the medial canthal tendon. The radix artery divided into two opposite branches: the dorsal nasal artery going to the nose and the paracentral artery going to the glabella. Ultrasound imaging revealed a subcorrugator space that a cannula can safely pass through. At the supraorbital foramen/notch, the supraorbital artery traveled very close to the bone. Based on the anatomical data collected, the following injection points for a needle and a cannula technique are recommended. Conclusion: Correction of a sunken upper eyelid is a dangerous procedure which should be performed only by experienced physicians. However, with precise anatomical knowledge and correct techniques, optimal outcomes can be safely achieved.